Developing a simple Swift application - Nugent, Tim; Manning, Jonathon; Buttfield-Addison, Paris (O'Reilly Media, Inc., 2016)
This lesson covers the basics of Apple's developer program and guides you through a simple Swift app. The lesson takes a very hands-on approach: you'll learn by programming. What you'll learn--and how you can apply it Design the interface for a simple iOS application. Create connections between your code and your interface. Learn to test out iOS applications using the iOS Simulator. This lesson is for you because ... You're a developer for OS X, iOS, or watchOS, and you want to learn how to develope apps using Swift Prerequisites None Materials or downloads needed None About the instructors Paris Buttfield-Addison is a producer and co-founder at Secret Lab, a mobile development studio based in beautiful Hobart, Australia. Secret Lab builds games for mobile devices, and primarily for children, such as the AIMIA winning (2014) ABC Play School apps for iPad. Paris formerly worked with Meebo (which was acquired by Google) as mobile product manager. He has a BA in History, and a PhD in Computing/HCI, and has written nearly a dozen technical, game design, and mobile development books, mostly for O'Reilly Media. Paris can be found on Twitter @parisba. He still thinks digital watches are a pretty neat idea. For more info visit Secret Lab or paris.id.au. Jon Manning is a world renowned iOS development trainer and writer, game designer, and mobile software engineering wizard. He has co-authored two books on mobile development and enjoys reimplementing such things as OpenGL and the Objective-C runtime (in his spare time). Jon is also a researcher in Human-Computer Interaction working towards a PhD. Tim Nugent pretends to be a mobile app developer, game designer, PhD student, and now he even pretends to be an author. When he isn't busy avoiding being found out as a fraud, he spends most of his time designing and creating little apps and games he won't let anyone see. Tim spent a disproportionately long time writing this tiny little bio, most of which was spent trying to stick a witty sci-fi reference in, before he simply gave up. Tim can be found as @The_McJones on Twitter.